The Impact of the International Human Rights Regime on Personal Security: A Comparative Study of South Africa and Saudi Arabia - Ragooloo, Prebashnee (University of the Witwatersrand, Johannesburg, 2023)
Personal security has become an important issue area to the international community since its differentiation as an aspect of human security (United Nations Human Development Report 1994, 25). The protection of the personal security of people is reliant on international and domestic criminal justice systems. The personal security of people within territories of democratic forms of government are expected to be more protected. Using a comparative method of analysis, South Africa and Saudi Arabia have been selected for this study due largely to the different types of government to determine the degree of personal security that people have in the respective countries. Unexpectedly, Saudi Arabia offers a greater protection of personal security to people within its territory due to the harsh punishments it administers to perpetrators of violent crime. The findings of the study indicate that democracies do not offer greater protection to people from physical violence as a result of its compassionate criminal justice laws. On the other hand, while authoritarian forms of government such as Saudi Arabia is viewed negatively, it affords people within its territory greater protection from violent crime. This study has found that a non-democratic regime (Saudi Arabia in this case) is found to be better a ensurer of personal security than a democratic regime. A key recommendation for future study could be that of comparing a greater number of democratic and non-democratic regimes and to gauge what a bigger sample of comparison could deliver.
A thesis submitted in fulfilment of the requirements for the degree: Master of Arts (International Relations) to the Faculty of Humanities, School of Social Sciences, University of Witwatersrand, Johannesburg, 2023.
Keywords: Personal security; Human security; Domestic criminal justice systems; International criminal justice systems; South Africa; Saudi Arabia; Violent crime; Physical violence; Criminal justice laws; UCTD; SDG-16: Peace, justice and strong institutions